Reconfigurable Dynamic Cellular Manufacturing System: A New Bi-Objective Mathematical Model. Issue 1 (10th January 2014) - Rabbani, Masoud; Samavati, Mehran; Ziaee, Mohammad Sadegh; Rafiei, Hamed
Abstract : Dynamic Cell Formation Problem (DCFP) seeks to cope with variation in part mix and demands using machine relocation, replication, and removing; whilst from practical point of view it is too hard to move machines between cells or invest on machine replication. To cope with this deficiency, this paper addresses Reconfigurable Dynamic Cell Formation Problem (RDCFP) in which machine modification is conducted instead of their relocation or replication in order to enhance machine capabilities to process wider range of production tasks. In this regard, a mixed integer nonlinear mathematical model is proposed, which is NP-hard. To cope with the proposed model's intractability, an Imperialist Competitive Algorithm (ICA) is developed, whose obtained results are compared with those of Genetic Algorithm's (GA's), showing superiority and outperformance of the developed ICA.